2005
DOI: 10.1111/j.1365-313x.2005.02415.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a putative voltage‐gated Ca2+ channel as a key regulator of elicitor‐induced hypersensitive cell death and mitogen‐activated protein kinase activation in rice

Abstract: SummaryElicitor-triggered transient membrane potential changes and Ca 2þ influx through the plasma membrane are thought to be important during defense signaling in plants. However, the molecular bases for the Ca 2þ influx and its regulation remain largely unknown. Here we tested effects of overexpression as well as retrotransposon (Tos17)-insertional mutagenesis of the rice two-pore channel 1 (OsTPC1), a putative voltage-gated Ca 2þ -permeable channel, on a proteinaceous fungal elicitor-induced defense respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 69 publications
3
103
1
3
Order By: Relevance
“…Previous studies have established the requirement of cytosolic Ca 2þ accumulation in the initiation of oxidative burst (Blume et al, 2000;Sagi and Fluhr, 2001;Kurusu et al, 2005). This conclusion is mainly deduced from the inhibition of elicitor-stimulated oxidative burst, particularly the second accumulation phase in the biphasic ROS production profile, by calcium chelators or channel blockers in cell cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have established the requirement of cytosolic Ca 2þ accumulation in the initiation of oxidative burst (Blume et al, 2000;Sagi and Fluhr, 2001;Kurusu et al, 2005). This conclusion is mainly deduced from the inhibition of elicitor-stimulated oxidative burst, particularly the second accumulation phase in the biphasic ROS production profile, by calcium chelators or channel blockers in cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cytosolic Ca 2þ accumulation is required for ROS production in plant cells (Jabs et al, 1997;Sagi and Fluhr, 2001;Kurusu et al, 2005). To test the effect of Ca 2þ on the interaction of Os Rac1 and Os rboh in vivo, FRET (A) GST pull-down assay.…”
Section: Fret Analysis Of Os Rac1-rbohb Interaction In Rice Protoplastsmentioning
confidence: 99%
“…14,15 Membrane fractionation by two-phase partitioning and immunoblot analyses revealed that OsTPC1 is localized predominantly at the PM. Whole cell patch clamp analyses of OsTPC1 heterologously expressed in HEK293T cells showed its voltagedependent Ca 2+ -permeability, indicating that OsTPC1 plays a crucial role in TvX-induced Ca 2+ influx as a PM Ca 2+ -permeable channel consequently required for the regulation of defense responses in cultured rice cells.…”
Section: Intracellular Localization and Physiological Function Of A Rmentioning
confidence: 99%
“…[17][18][19] In contrast, TPCs in monocots including OsTPC1 have been suggested to be localized at the PM and confirmed by several groups independently. [13][14][15]20 To resolve this discrepancy, and confirm the intracellular localization of TPC family proteins, we introduced a GFP construct fused to the coding sequence of the C-terminus of OsTPC1 (OsTPC1-GFP) -d, f-h) and differential interference contrast (DIC) images (a, e) of tobacco BY-2 cells expressing GFP (a-d) or OsTPC1-GFP (e-h) stained with the fluorescent styryl membrane probe FM4-64 (Molecular Probes, USA). Scale bar: 20 μm.…”
Section: Intracellular Localization Of Ostpc1mentioning
confidence: 99%
“…13 The key signaling events connecting 2 phases of oxidative burst are calcium channel activation and protein phosphorylation events. 6,11,13,14 Realtime detections of both SA-induced ROS generation (especially of O 2 ¡ ) and SAinduced increase in cytosolic calcium concentration were first performed by our group by using Cypridina luciferin analog (CLA)-treated and aequorin-expressing model plant cells (tobacco BY-2 cells). 11,15 To date, known earliest signaling event in response to exogenously added SA is the cell wall peroxidase-catalyzed generation of O 2 ¡ in a H 2 O 2 -dependent manner.…”
Section: Introductionmentioning
confidence: 99%